Innovative activity of small business in the structure of GDP (Journal of Economic Research & Business Administration, 2017)
The article considers the role of innovative activity of small business inthe structure of GDP. Nowadays when the economic situation in the worldis unstable, different countries are trying to reach economic growth by differenteffective ways. One of such tools is developing innovative activityof small and medium entrepreneurship in the structure of GDP. The articlealso considers the experience of developed countries, because the share ofSME in GDP is more than 50%. Accordingly, one of the main aims of ourGovernment is to provide witj necessary resources all entrepreneurs whoare eager to get state support. On the other hand, the comparative analysisof different regions and cities of Kazakhstan by their innovative activity insmall business is done.